Aplicación de una auditoría tributaria a la ferretería comercial Jácome & Corrales cía. ltda. ubicada en el sector la estación parroquia Eloy Alfaro cantón Latacunga provincia de Cotopaxi, al período comprendido del 01 de enero al 31 de diciembre del año 2013 - Rivadeneira Erazo, Ximena Germania (2015)
In this research were used bibliographic references, also used the descriptive and census methodology, inasmuch as analyzed the real economic and fiscal situation of the company through statistical data, alike were applied data collection techniques , such as observation, interview and survey, and finally to the review of data collected was applied the descriptive statistical method, being that performed the interpretation and review of either one data, note that was analyzed the data collected from the population or universe of the company, through the investigation was determined a level of low risk and a and high confidence, resulting in good internal control. It was established the default value of tax credit in the I.V.A of September 2013.